Synthesis of Thresholds of Ocean Acidification Impacts on Decapods - Bednaršek, Nina; Ambrose, Richard; Calosi, Piero; Childers, Richard K.; Feely, Richard A.; Litvin, Steven Y.; Long, W. Christopher; Spicer, John I.; Štrus, Jasna; Taylor, Jennifer; Kessouri, Faycal; Roethler, Miranda; et al. (Frontiers in Marine Science, 2021)
Assessing decapod vulnerability to regional-scale ocean acidification (OA) conditions is limited because of a fragmented understanding of the thresholds at which they exhibit biological response. To address this need, we undertook a three-step data synthesis: first, we compiled a dataset composed of 27,000 datapoints from 55 studies of decapod responses to OA. Second, we used statistical threshold analyses to identify OA thresholds using pH as a proxy for 13 response pathways from physiology to behavior, growth, development and survival. Third, we worked with the panel of experts to review these thresholds, considering the contributing datasets based on quality of the study, and assign a final thresholds and associated confidence scores based on quality and consistency of findings among studies. The duration-dependent thresholds were within a pH range from 7.40 to 7.80, ranging from behavioral and physiological responses to mortality, with many of the thresholds being assigned medium-to-high confidence. Organism sensitivity increased with the duration of exposure but was not linked to a specific life-stage. The thresholds that emerge from our analyses provide the foundation for consistent interpretation of OA monitoring data or numerical ocean model simulations to support climate change marine vulnerability assessments and evaluation of ocean management strategies.